2009
DOI: 10.1371/journal.ppat.1000412
|View full text |Cite
|
Sign up to set email alerts
|

Recombination between Polioviruses and Co-Circulating Coxsackie A Viruses: Role in the Emergence of Pathogenic Vaccine-Derived Polioviruses

Abstract: Ten outbreaks of poliomyelitis caused by pathogenic circulating vaccine-derived polioviruses (cVDPVs) have recently been reported in different regions of the world. Two of these outbreaks occurred in Madagascar. Most cVDPVs were recombinants of mutated poliovaccine strains and other unidentified enteroviruses of species C. We previously reported that a type 2 cVDPV isolated during an outbreak in Madagascar was co-circulating with coxsackieviruses A17 (CA17) and that sequences in the 3′ half of the cVDPV and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 66 publications
3
109
1
3
Order By: Relevance
“…Breakpoints between Sabin strains were concentrated in the 2C and 3C regions ( Fig. 3 and Table 1), consistent with previous observations (19,21,22,67 ]. To put our Sabin-like recombination fixation results in context, we compared them with those for the index case isolates of known cVDPV emergences in Nigeria (19).…”
Section: Per Base Substitution Rates For Nonrecombinant Samplessupporting
confidence: 91%
See 1 more Smart Citation
“…Breakpoints between Sabin strains were concentrated in the 2C and 3C regions ( Fig. 3 and Table 1), consistent with previous observations (19,21,22,67 ]. To put our Sabin-like recombination fixation results in context, we compared them with those for the index case isolates of known cVDPV emergences in Nigeria (19).…”
Section: Per Base Substitution Rates For Nonrecombinant Samplessupporting
confidence: 91%
“…However, previous studies have indicated that in Sabin strains, reversion of known attenuating sites can occur within the duration of a single infection and that VP1 substitutions accumulate more quickly than would be expected from the wild-type neutral substitution rate; multiple VP1 substitutions occur within the first month after administration of the vaccine dose (10)(11)(12)(13)(14)(15). In addition, most reported cVDPV isolates are recombinants with Sabin-derived capsid and enterovirus C (poliovirus and nonpoliovirus) noncapsid sequences, although the role of selection pressure in this process is not clear (1,2,11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). cVDPV has become a significant source of poliomyelitis.…”
mentioning
confidence: 99%
“…Generation of PVs from`non-infectious' oligo nucleotides have provoked novel discussions on biosecurity issues relevant to the eradication program (97). In addition, analysis of picornavirus genomes has revealed that the non-structural protein-coding region of the PV genome is largely equivalent to those of PV-like Enterovirus species C (coxsackie A virus types 11, 17, and 20) in terms of amino acid sequence identity (more than 95z identity with PV sequences) (31) and compatibility with the PV capsid (i.e., some coxsackie A viruses can use the PV capsid for the production of infectious virus) (25,(98)(99)(100). Thus, the PV-like non-structural proteincoding region is circulating in the field with coxsackie A virus capsid, which could not be the target for the eradication program until severe clinical symptoms like poliomyelitis with high attack rate are identified.…”
Section: Perspectivesmentioning
confidence: 99%
“…Les CVA-17 et CVA-13 seraient des partenaires privilégiés de recombinaison avec le PV. Nos études in vitro ont confirmé que ces virus sont des partenaires de recombinaison compatibles [18]. Il n'est pas possible, à l'heure actuelle, d'exclure totalement l'hypothèse selon laquelle la recombinaison intertypique chez les HEV-C serait une conséquence 2 Un virus recombinant intratypique est le produit de la recombinaison entre deux ou plusieurs virus de même sérotype (par exemple : PV souche sauvage de type 1/PV souche Sabin 1), alors qu'un virus recombinant intertypique est le produit de la recombinaison entre deux ou plusieurs virus de sérotypes différents (par exemple : PV souche Sabin 2/ PV souche Sabin 3, ou PV souche Sabin 2/CVA 17).…”
Section: Les Autres éPidémies Dans Le Mondeunclassified